Evaluation of clinical and prognostic features and treatment outcomes in patients with chronic lymphocytic leukemia - Ekinci, Omer; Turgut, Ergin (Mattioli 1885, 2021)
Objective: We aimed to investigate the demographic and clinicopathologic characteristics, treatment responses, survival rates, and prognostic factors affecting survival in patients with chronic lymphocytic leukemia (CLL). Material and Methods: We retrospectively evaluated a total of 131 patients with CLL and-divided into two groups, alive and deceased, based on their situation at the time the data were collected for comparison. Results: The majority of the patients were male (n = 95; 72.5%) and the median age was 62 (35-82) at disease baseline. The mean follow-up time was 31.7 months and overall 3- and 5-year survival rates (OS) were 93.4% and 87.4%, respectively, for all patients. There were significant differences between the alive and deceased group with respect to age, platelet count, hemoglobin level, lactate dehydrogenase, albumin, Rai, modified Rai, and Binet stages, B symptoms, splenomegaly, hepatomegaly and autoimmune hemolytic anemia (AIHA) < 0.05). Regardless of treatment regimen, the treatment response rate in patients receiving first-line treatment was better in alive than in deceased (p < 0.001). Multivariate Cox regression analysis showed the following independent prognostic factors to affect both overall survival (OS) and treatment-free survival (TFS): age <= 64, Binet <= stage B, B symptoms, albumin > 4.1 g/dL, and presence of hepatomegaly. Also, AIHA was an independent prognostic factor affecting only TFS rates. Conclusion: The demographic characteristics of our patients were consistent with the literature, while our 3- and 5-year survival rates were higher. Notably, hepatomegaly and hypoalbuminemia were associated with low OS and TFS. The limitation of the study was the lack of a clear comparison between treatment regimens due to the uneven distribution of the number of patients receiving treatment.
Keywords: Chronic lymphocytic leukemia; prognostic factors; survival